Analysis of Deep Structure and Surface Structure in CNN Indonesia News "The Chain Effect of Smart and Accurate" from the Perspective of Chomsky's Theory - Hadi, Ali Mansur (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Study aims to analyze the deep structure and surface structure of CNN Indonesia's news article entitled "Efek Berantai Cerdas Cermat" based on Noam Chomsky's generative grammar theory. The method used in this study is a qualitative descriptive method with a listening and note-taking technique. The research data are in the form of sentences in online news articles that contain syntactic transformations, such as changes in active and passive structures, phrases, and complex clauses. The analysis is carried out by identifying the deep structure and surface structure of each piece of data based on the rules of generative grammar. The results of the study indicate that the article contains various forms of syntactic transformations that affect the surface structure of the sentence without changing its basic meaning. The use of sentence structure in the article also shows the application of effective syntactic patterns to convey information to readers. This study concludes that Chomsky's generative grammar theory is relevant for use in analyzing sentence structures in Indonesian online news media.